Artocarpus altilis extracts as a foodborne pathogen and oxidation inhibitors: RSM, COSMO RS, and molecular docking approaches - Ahmad, Mohammad Norazmi; Karim, Nazatul Umira; Abdullah, Erna Normaya; Mat Piah, Mohd Bijarimi; Iqbal, Anwar; Ku Bulat, Ku Halim (Springer Nature, 2020)
Lipid oxidation and microbial contamination are the major factors contributing to food deterioration. Food additives like antioxidants and antibacterials can prevent food spoilage by delaying oxidation and preventing the growth of bacteria. Artocarpus altilis leaves exhibited biological properties that suggested its use as a new source of natural antioxidant and antimicrobial. Supercritical fuid extraction (SFE) was used to optimize the extraction of bioactive compounds from the leaves using response surface methodology (yield and antioxidant activity). The optimum SFE conditions were 50.5°C temperature, 3784psi pressure and 52min extraction time. Verifcation test results (Tukey’s test) showed that no signifcant diference between the expected and experimental DPPH activity and yield value (99%) were found. Gas-chromatography –mass spectrometry (GC-MS) analysis revealed three major bioactive compounds existed in A. altilis extract. The extract demonstrated antioxidant and antibacterial properties with 2,3-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, ferric reducing ability of plasma (FRAP), hydroxyl radical scavenging activity, tyrosinase mushrrom inhibition of 41.5%, 8.15±1.31 (µg of ascorbic acid equivalents), 32%, 37% and inhibition zone diameter of 0.766±0.06cm (B. cereus) and 1.27±0.12cm (E. coli). Conductor like screening model for real solvents (COSMO RS) was performed to explain the extraction mechanism of the major bioactive compounds during SFE. Molecular electrostatic potential (MEP) shows the probability site of nucleophilic and electrophilic attack during bacterial inhibition. Based on molecular docking study, non-covalent interactions are the main interaction occurring between the major bioactive compounds and bacteria (antibacterial inhibition).